Anterior cruciate ligament injury in National Collegiate Athletic Association basketball and soccer - A 13-year review - Agel, J.; Arendt, E. A.; Bershadsky, B. (The American Journal of Sports Medicine, 2005)
Background: Female collegiate athletes have been reported to have a higher rate of anterior cruciate ligament injury compared to male collegiate athletes. This finding has spawned a branch of research focused on understanding and preventing this injury pattern.